MENCARI KEBENARAN MATERIIL DALAM “HARD CASE” PENCURIAN TIGA BUAH KAKAO - Widodo Dwi Putro (Jurnal Yudisial, 2010)
ABSTRACTLegal certainly and justice are two values that are often persevere in the formulation of the judge's decisions. This is more prominent, when judges face cases categorized as "hard cases" one of which is the decision of the case of three cocoa, which are analyzed in this paper. The authors appreciate this decision because the judges do not just read the rules and laws, but also use their conscience so that this decision really give justice to the convict. The author points out there are so many non-legal aspects that go behind the formulation of a written decision. The case looks simple on paper. For example, in this case we can really go through even further into the root causes of a more macro level, namely the existence of land conflicts in the area. In view of that, we can resolve that good judge's decision will be born from an intense struggle in search of material truth in every case.Keywords: hard case, clear case, legal reasoning. ABSTRAKKepastian hukum dan keadilan merupakan dua nilai yang selalu terformulasikan dalam putusan hakim. Hal itu akan semakin melekat pada saat hakim menghadapi kasus yang termasuk kategori "kasus sulit" seperti kasus Pencurian Kakao yang menjadi analisa dalam tulisan ini. Penulis sangat menghargai putusan ini karena tidak hanya merujuk pada hukum dan undang-undang, tetapi juga mengunakan pendekatan keadilan bagi terdakwa. Penulis mengambil hal penting bahwa ada aspek non hukum dibalik formulasi putusan yang tertulis. Kasus ini terlihat simpel karena menyangkut konflik area pertanahan sebagai akar masalah. Dalam kasus ini secara sederhana, kita dapat menyimpulkan bahwa putusan hakim yang baik akan lahir ketika adanya usaha secara intensif untuk mendapatkan kebenaran secara materiilKata kunci: kasus yang sulit, kasus yang jelas, alasan hukum